The usage of sustained-action theophyline in the intercrisis treatment of bronchial asthma. - Yaquelín Martínez Chavez.; Arlette Linares Borges.; Pedro Miguel Milián Vázquez.; Lisett Jiménez Fernández.; Maira Quirós Enríquez.; Higinio Alemán Aguiar (Medisur)
Fundaments: Bronchial Asthma is a chronic inflammatory disease of the air ways. Theophylline is recommended in its treatment because of its probable anti-inflamatory effect. Due to this reason, the clinical effect of sustained action theophylline (TEOCEN 200mg) is assessed in the intercrisis of Bronchial Asthma. Method : 40 moderate and severe asthmatic patients received treatment with a 9 mg/kg/day dose every 12 hours (q.12), at the outpatient consultation of the University Hospital Celestino Hdez¨ of Villa Clara, from September 2002 to June 2003. Treatment lasted a month, period in which had 5 visits to the doctor. The variables under study in each visit were: attendance to the emergency department, use of salbutamol spray and objective measurement of lung function as well as adverse effects and response to treament. Wilconxon, Cochron Q and Mc. Nemor´s non-parametric tests were used in this study. Significant difference was considered as p< 0, 05, highly significant difference as p< 0,01. Results : The use of salbutamol spray and the need to go to the emergency department diminished significantly meanwhile the peak expiratory flux, the forced expiratory volume in one second, the maximum expiratory medium flux and the forced expiratory volume in one second post salbutamol application increased significantly. There was a low incidence of adverse effects. Conclusion : The formula was useful and is recommended in the control of the symptoms of moderate and severe asthmatic patients in the intercrisis period.